Comparison of the use of intravenous iron sucrose with intravenous ferric Carboxymaltose for treatment of iron deficiency anaemia in pregnant patients - Khir-Un Nisa; Rukhsana Shaheen Afzal; Faiza Safdar; Noreen Majeed; Shabana Kalsoom; Irum Mushtaq (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Iron deficiency results in major disabilities and death all over the world, about two billion people are suffering from anaemia at the moment. To compare intravenous iron sucrose with intravenous ferric carboxymaltose in terms of mean change in hemoglobin level and mean corpuscular volume (MCV) for treatment of iron deficiency anaemia in pregnant patients. METHODOLOGY: Prospective comparative study was conducted at the department of Obstetrics/ Gynecology of POF Hospital Wah Cantt and HIT Hospital Taxila Cantt. The study duration was 2 years, from January 2017-December 2018. A total of 80 patients were included in the study. Patients were randomly divided into two groups; in Group-A; 40 patients were given intravenous iron sucrose, and in Group B, 40 patients were given intravenous ferric carboxymaltose. Patients were observed for hemoglobin level and mean corpuscular volume (MCV). Data analysis was done with SPSS version 24. An Independent t-test was applied, and results with p-value ≤0.05 were found significant. RESULTS: Post-treatment hemoglobin means level in the iron sucrose group was 9.90±0.4SD, and in the intravenous ferric carboxymaltose group, post-treatment hemoglobin was 10.71±0.9SD (p≤0.001). In the iron sucrose group, the post-treatment mean corpuscular volume mean level was 81.94±6.0SD and in the intravenous ferric carboxymaltose group mean post-treatment mean corpuscular volume was 88.08±7.1SD (p≤0.001) CONCLUSION: Treatment with intravenous iron caboxymaltose is superior to intravenous iron sucrose with respect to hematological response, which seems to be safe, as very few severe side effects were observed.